2011
DOI: 10.1016/j.jpain.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Pain Sensitivity Risk Factors for Chronic TMD: Descriptive Data and Empirically Identified Domains from the OPPERA Case Control Study

Abstract: Many studies report that people with temporomandibular disorders (TMD) are more sensitive to experimental pain stimuli than TMD-free controls. Such differences in sensitivity are observed in remote body sites as well as in the orofacial region, suggesting a generalized upregulation of nociceptive processing in TMD cases. This large case-control study of 185 adults with TMD and 1,633 TMD-free controls measured sensitivity to painful pressure, mechanical cutaneous, and heat stimuli, using multiple testing protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
218
4
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(252 citation statements)
references
References 36 publications
15
218
4
6
Order By: Relevance
“…No correlation was found to CPT tolerance. In other words, clamp pain intensity correlated to other QST to varying degrees, which is in line with the literature which suggests, that different methods of QST measure different aspects of pain sensitivity and modulation [6,7,18,19].…”
Section: Correlationsupporting
confidence: 90%
See 2 more Smart Citations
“…No correlation was found to CPT tolerance. In other words, clamp pain intensity correlated to other QST to varying degrees, which is in line with the literature which suggests, that different methods of QST measure different aspects of pain sensitivity and modulation [6,7,18,19].…”
Section: Correlationsupporting
confidence: 90%
“…Different QST procedures measure different aspects of pain sensitivity, whilst others overlap to some degree [6][7][8]. The pressure algometer is often used to assess pain detection thresholds of deep-tissue structures [9], but quantifying the effects of temporal summation or conditioned pain modulation (CPM), require a more complicated set-up [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual's pain threshold at baseline (i.e., while asymptomatic) was a strong predictor of the development of TMJD, as any individual on the "hyperalgesic side" of a bell-shaped curve of pain sensitivity at baseline was nearly 3Â as likely to develop TMJD as an individual in the bottom half of pain sensitivity. These results have recently been replicated in a much larger cohort, and they showed that pressure pain threshold was the single experimental measure of pain threshold with respect to predicting the future onset of TMJD [54].…”
Section: Introductionmentioning
confidence: 77%
“…The current model of the susceptibility for developing TMD includes anatomical, neuromuscular, and psychological factors that operate in parallel, reflecting the concerted effects of genetic and non-genetic etiological factors. [35][36][37][38] The OPPERA project began by recruiting 3,300 healthy women who were followed up for five years with the expectation that about 10% would develop TMD over the course of the study. By having participants respond to psychological questionnaires, questionnaires that describe various aspects of TMD pain, and a number of psychophysical and cardiovascular assays, this project identified non-genetic risk factors for TMD.…”
Section: Pain Genetics: Ongoing Studiesmentioning
confidence: 99%